Pengembangan 3D Virtual Learning Environment - Kusuma, Rahma Djati; Pradana, Egi Adithia Adithia (Jurnal Ilmiah Manajemen Kesatuan, 2019)
Virtual learning environment (VLE) has become an integral part of modern education. In the era of technology, students are using smartphone and computer in everyday learning. The use of computers for learning is diverse, starting from the simple thing like for reading e-books and learning materials to doing simulation. On the other hands, students are very familiar with computer games. 3D VLE offers learning process using media that looks like game so that students are motivated to learn and do the challenges given. Keywords: virtual learning, virtual learning environment, education